KOMUNIKASI PERSUASIF BALAI TAMAN NASIONAL KOMODO KABUPATEN MANGGARAI BARAT DALAM MENCEGAH PERBURUAN SATWA LIAR - Maria Karina Winny Naro; Kadek Devi Kalfika Anggria Wardani; Putri Ekaresty Haes; Putu Dyah Permatha Korry (Journal of Innovation Research and Knowledge, 2025)
This study aims to describe the persuasive communication strategies implemented by the Komodo National Park Authority in preventing wildlife poaching in West Manggarai Regency. Wildlife poaching poses a serious threat to the sustainability of Komodo dragons and their primary prey, such as the Timor deer, thereby disrupting ecosystem balance and increasing the risk of human wildlife conflict. Although law enforcement efforts have been carried out, behavioral change within local communities cannot be achieved solely through legal measures without the support of effective and human-centered communication strategies. This research employs a qualitative descriptive approach using in-depth interviews, non-participant observation, and document analysis. The Yale Model of Persuasive Communication serves as the analytical framework to evaluate the effectiveness of the communicator, message construction, communication channels, and the stages of message learning, including attention, comprehension, learnability, acceptance, and retention. The findings indicate that the credibility of communicators such as Forest Rangers and respected community leaders plays a significant role in increasing message acceptance. Messages combining rational appeals with emotional narratives are proven to be more effective in fostering ecological awareness and empathy. Additionally, direct outreach and community-based counseling within conservation areas emerge as the most influential communication channels due to their personal and contextually relevant nature. In conclusion, persuasive communication serves as a strategic tool in building awareness, shaping attitudes, and encouraging behavioral change to reduce wildlife poaching. This study highlights the importance of integrating persuasive communication with conservation management as a long-term preventive strategy